Perencanaan Ulang Sistem Saluran Drainase di Kecamatan Menganti Kabupaten Gresik - Dandy Nugroho; Bowo Leksono; Irani Sholikhah (Wahana Teknik, 2021)
Sub district Menganti is one of sub districts of the district of Gresik. The region during the rainy season is often suffered flooding. The flooding problem is likely to arise as result of inadequate channels capacity, changes in land use, drainage network system which is not connected properly, and the lack of public awareness of the importance of maintaining the drainage channels, as well. The final project aims to design the drainage system in the sub district of Menganti-Gresik. Drainage is also interpreted as an effort to control groundwater quality in relation to salinity. The purpose of this study is to plan drainage channels in the Menganti District, Gresik Regency. Data or information used is secondary data obtained from the Public Works Department and primary data obtained from direct surveys in the field. The data processing method uses manual calculation in accordance with the rational method for calculating rain discharges, and the manning formula for channel discharges. The conclusions that can be drawn from this research are: 1) Floods that occur are caused by many areas that do not have a well-integrated drainage network system. 2) The design flow velocity for secondary drainage is 1.93–3.19 m/s. The dimensions of the secondary drainage channel are rectangular with variations in width 0.94–2.28 m and channel height 0.47–1.14 m. 3) The design flow velocity for primary drainage is 2.4–4.5 m/s. The dimensions of the primary drainage channel are rectangular with variations in width of 0.91–1.62 m and channel height 0.5–0.8 m. Keywords: drainage, gresik, menganti, re-planning